New evidence on the finite sample properties of propensity score matching and reweighting estimators - Matias Busso; John DiNardo; Justin McCrary (Institute for the Study of Labor (IZA), 2009)
Currently available asymptotic results in the literature suggest that matching estimators have higher variance than reweighting estimators. The extant literature comparing the finite sample properties of matching to specific reweighting estimators, however, has concluded that reweighting performs far worse than even the simplest matching estimator. We resolve this puzzle. We show that the findings from the finite sample analyses are not inconsistent with asymptotic analysis, but are very specific to particular choices regarding the implementation of reweighting, and fail to generalize to settings likely to be encountered in actual empirical practice. In the DGPs studied here, reweighting typically outperforms propensity score matching.
urn:nbn:de:101:1-20090304687
Keywords: C14; C21; C52; 330; Treatment effects; propensity score; semiparametric efficiency; Nichtparametrisches Verfahren; Schätztheorie; Stichprobenverfahren; Theorie